Solve for x
x=50
x=64
Graph
Share
Copied to clipboard
-10x^{2}+1140x-29600=2400
Swap sides so that all variable terms are on the left hand side.
-10x^{2}+1140x-29600-2400=0
Subtract 2400 from both sides.
-10x^{2}+1140x-32000=0
Subtract 2400 from -29600 to get -32000.
x=\frac{-1140±\sqrt{1140^{2}-4\left(-10\right)\left(-32000\right)}}{2\left(-10\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -10 for a, 1140 for b, and -32000 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-1140±\sqrt{1299600-4\left(-10\right)\left(-32000\right)}}{2\left(-10\right)}
Square 1140.
x=\frac{-1140±\sqrt{1299600+40\left(-32000\right)}}{2\left(-10\right)}
Multiply -4 times -10.
x=\frac{-1140±\sqrt{1299600-1280000}}{2\left(-10\right)}
Multiply 40 times -32000.
x=\frac{-1140±\sqrt{19600}}{2\left(-10\right)}
Add 1299600 to -1280000.
x=\frac{-1140±140}{2\left(-10\right)}
Take the square root of 19600.
x=\frac{-1140±140}{-20}
Multiply 2 times -10.
x=-\frac{1000}{-20}
Now solve the equation x=\frac{-1140±140}{-20} when ± is plus. Add -1140 to 140.
x=50
Divide -1000 by -20.
x=-\frac{1280}{-20}
Now solve the equation x=\frac{-1140±140}{-20} when ± is minus. Subtract 140 from -1140.
x=64
Divide -1280 by -20.
x=50 x=64
The equation is now solved.
-10x^{2}+1140x-29600=2400
Swap sides so that all variable terms are on the left hand side.
-10x^{2}+1140x=2400+29600
Add 29600 to both sides.
-10x^{2}+1140x=32000
Add 2400 and 29600 to get 32000.
\frac{-10x^{2}+1140x}{-10}=\frac{32000}{-10}
Divide both sides by -10.
x^{2}+\frac{1140}{-10}x=\frac{32000}{-10}
Dividing by -10 undoes the multiplication by -10.
x^{2}-114x=\frac{32000}{-10}
Divide 1140 by -10.
x^{2}-114x=-3200
Divide 32000 by -10.
x^{2}-114x+\left(-57\right)^{2}=-3200+\left(-57\right)^{2}
Divide -114, the coefficient of the x term, by 2 to get -57. Then add the square of -57 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-114x+3249=-3200+3249
Square -57.
x^{2}-114x+3249=49
Add -3200 to 3249.
\left(x-57\right)^{2}=49
Factor x^{2}-114x+3249. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-57\right)^{2}}=\sqrt{49}
Take the square root of both sides of the equation.
x-57=7 x-57=-7
Simplify.
x=64 x=50
Add 57 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}